REMEDIATION OF LEAD (II) AND MALACHITE GREEN FROM AQUEOUS SOLUTION USING PALM OIL FRUIT FIBRE - OOI, Shin-Leei; ONG, Siew-Teng (Studia Universitatis Babeș-Bolyai Chemia, 2019)
Oil palm fruit fibre (OPFF) was investigated for its potential and probability to remove heavy metal ion and dye from the aqueous solutions. Different operational parameters were studied under batch experiment. The effective pH to attain maximum adsorption of MG and Pb(II) by OPFF was around pH 4 to 5. The adsorption process was rapid at the beginning and slowly achieved equilibrium within 180 minutes and 120 minutes for MG and Pb(II), respectively. From the experimental result, the pseudo-second-order kinetic model provided better correlation compared to pseudo-first-order kinetic model with R2 > 0.999. Various isotherm equations, such as Langmuir, Freundlich, and BET isotherm models were used to analyze the adsorption isotherm result. The experimental data fitted well into Langmuir and BET isotherm models with R2 = 0.996 and 0.984, respectively. The maximum adsorption capacity of OPFF from Langmuir equation was 41.67 and 10.10 mg/g for MG and Pb(II), respectively. Besides, characterization study of OPFF which include point of zero charge (pHzpc), chemical modification on the functional group and surface morphology was also performed in this study.